Sicut Lilium inter Spinas: Literature and Religion in the Renaissance - Caporicci, Camilla (utzverlag GmbH, 2018)
The relationship between literature and religion is a crucial element in the definition of every cultural system. Literary traditions developed in such close connection with religious thought, symbolism, institutions and practices, that our understanding of both literary and religious expressions of an age necessarily depends on our consideration of their interconnectedness. This is particularly true for such a controversial age as the European Renaissance: a period that witnessed the rise of national states and the great Catholic-Protestant schism; a rediscovery of classical antiquity and a new approach to the biblical text; the flourishing of literature and art and strong politico-religious censorship; a definite advancement in philosophical, scientific and political thought, and a profound redefinition of the relationships and boundaries between the sacred and profane. By taking into account different literary and cultural systems, and being open to a plurality of approaches, this volume explores the relationship between literature and religion in a period crucial to the development of European cultural identity, offering both innovative readings of world-famous works and a (re)discovery of less familiar texts.   Reihe Münchener Italienstudien - Band 6